Factores psicosociales relacionados al conocimiento sobre el VIH/SIDA en adolescentes de decimo a undécimo grado. (2022)
The general objective of this project is to establish the relationship between psychosocial factors and knowledge about HIV/AIDS in adolescents from tenth to eleventh grade of the Livio Reginaldo Fischione school with a quantitative approach and a non-experimental design, the confidential questionnaire was applied. on active sexual life and the CAP scale on HIV/AIDS to a total of 60 young people from the department of La Guajira, Colombia. It was evidenced that although more than 50% of the students claim to maintain good sexual and protective behavior, there is a group greater than 10% that ignores protective behaviors against sexually transmitted diseases, which creates an alert that is linked to it. increased initiation of sexual activity at an early age becomes a risk that must be addressed.